2021
DOI: 10.1016/j.gerinurse.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a mortality predictor in older adults with COVID-19: A systematic review and meta-analysis of cohort studies

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has caused the coronavirus diseases 2019 (COVID-19) pandemic, continues to spread rapidly worldwide and is associated with high rates of mortality among older adults, those with comorbidities, and those in poor physiological states. This paper aimed to systematically identify the impact of frailty on overall mortality among older adults with COVID-19. We conducted a systematic review of the literature indexed in 4 databases. A random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…The factors affecting frailty include a combination of deficiencies in strength, balance, motor processing, cognition, nutrition, endurance, and physical activity. 34 , 35 ) Our comparisons of the mean EFS scores before and 3 months after the intervention showed a significant difference between the OEG and CG (p=0.0001). Sadjapong et al 9 ) also reported a significant change (<0.01) in the frailty score of the intervention group compared to the control group.…”
Section: Discussionmentioning
confidence: 72%
“…The factors affecting frailty include a combination of deficiencies in strength, balance, motor processing, cognition, nutrition, endurance, and physical activity. 34 , 35 ) Our comparisons of the mean EFS scores before and 3 months after the intervention showed a significant difference between the OEG and CG (p=0.0001). Sadjapong et al 9 ) also reported a significant change (<0.01) in the frailty score of the intervention group compared to the control group.…”
Section: Discussionmentioning
confidence: 72%
“…before the onset of COVID 19 disease, estimated with the use of CFS. A number of recent studies demonstrated that the presence of severe frailty can stratify patients with COVID-19 at increased risk of in-hospital death, thus suggesting that the evaluation of frailty can support decision making about medical care in adult patients admitted to hospital with COVID-19 ( Covino et al, 2021 , Marengoni et al, 2021 , Rebora et al, 2021 , Saragih et al, 2021 , Yang et al, 2021 , Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors associated with mortality such as frailty have also been described in other studies involving older patients with COVID-19. For example, in a recent systematic review including data from 924,520 patients, frailty was found to increase more than five-fold the likelihood of COVID-19-associated mortality [ 49 ]. These findings have been also verified by other studies [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%